Issues in Theoretical Diversity Persistence, Composition, and Time - Miller, Kristie Lyn (Philosophical Studies Series, 2006)
Our world is full of composite objects that persist through time: dogs, persons, chairs and rocks. But in virtue of what do a bunch of little objects get to compose some bigger object, and how does that bigger object persist through time? This book aims to answer these questions, but it does so by looking at accounts of composition and persistence through a new methodological lens. It asks the question: what does it take for two theories to be genuinely different, and how can we know whether what seems like metaphysical disagreement is really just semantic disagreement? By offering a framework within which to explore issues of theoretical diversity, this book provides a novel way of thinking about the inter-relationship between composition and persistence. Ultimately, it argues for a new way of thinking about these issues, a way that does not preserve the standard theoretical dichotomies between four-dimensionalist theories on the one hand, and three-dimensionalist theories on the other.